التماسك النحوي في سورة المجادلة و انعكاسه في تعلم اللغة العربية - Khoirunnisa; Ubaid Ridho (Comit: Communication, Information and Technology Journal, 2025)
The Qur'an, as a source of Arabic language principles, provides numerous examples of grammatical cohesion as the linguistic elements' operation to connect sentences and paragraphs, thereby creating a grammatically structured text, including in Surah Al-Mujadalah. This study aims to: 1) Identify grammatical cohesion in Surah Al-Mujadalah, 2) Describe the forms of grammatical cohesion in Surah Al-Mujadalah, 3) Determine the causes of grammatical cohesion, and 4) Explain its implementation in Arabic language teaching. This research employs a qualitative approach. Data collection was conducted through library research.The results reveal that grammatical cohesion in the Arabic language of the Qur'an is evident in the use of interrelated linguistic elements structurally. In Surah Al-Mujadalah, several forms of grammatical cohesion are identified, including: reference, conjunction, substitution, and ellipsis. Grammatical cohesion in Surah Al-Mujadalah is highly beneficial for Arabic language learning, particularly in understanding sentence structures and techniques for establishing meaning connections within sentences. In its implementation, the researcher used the Qawaid Method, which is beneficial for improving reading and writing skills. The results showed that in teaching using the Qawaid Method, examples of verses from Surah Mujadalah containing grammatical cohesion such as Reference, Substitution, Conjunction, and Ellipsis could be used. This implementation was carried out entirely in the preparation of the teacher's lesson plans (RPP) for Arabic Language Lesson under the Merdeka Curriculum in Indonesia.